CONTROL AND RESISTANCE IN A YOUNG ADULT DYSTOPIAN FICTION: A FOUCAULDIAN READING OF MARIE LU'S LEGEND - Amalina, Nur (2015)
This research attempts to discover how a young adult dystopian novel entitled Legend by Marie Lu portrays a totalitarian government controls its subjects, along with the way young adult characters resist the control. This research employs Foucault's discipline techniques and categorizations of resistance. The findings show that the controlling strategies in the society within Legend reflect two of Foucault's techniques: geneses organization, and distribution system.Additionally, the controlling strategy is supported by the use of terror and knowledge concealment. For the young adult resistance aspect, the resistance acts are directed towards subjection and domination. The resistance is manifested through actions which are either aggressive or submissive. In addition, Legend also demonstrates the use of discourse as a device for revolting. Ultimately, Legend appears to inherit the didactic nature of young adult dystopian literature as it casts warning about absolutism of a certain group, the danger of a certain policy in current society, and the importance of knowledge, individuality and freedom of choice. Keywords: control, resistance, discipline, dystopia, young adult Penelitian ini bertujuan untuk menelaah cara sebuah novel remaja distopia berjudul Legend karya Marie Lu menggambarkan pemerintahan totaliter mengontrol warganegaranya sekaligus cara karakter remaja melakukan perlawanan terhadap kontrol tersebut. Penelitian ini menerapkan teknik disiplin dan kategori pertentangan yang digagas oleh Foucault. Temuan penelitian menunjukkan bahwa strategi kontrol dalam masyarakat di novel Legend mencerminkan dua teknik Foucault: pengaturan genesis, dan sistem distribusi. Di samping itu, strategi untuk mengontrol didukung oleh penggunaan teror dan penyembunyian pengetahuan. Untuk aspek pertentangan, karakter remaja dalam novel mengarahkan pertentangan mereka terhadap dominasi dan subjeksi. Pertentangan itu sendiri dilakukan melalui dua aksi yang bersifat agresif atau subtil. Sebagai tambahan, Legend juga menggambarkan penggunaan tulisan sebagai perangkat perlawanan. Ditarik dari hasil penelitian, Legend terlihat mewarisi sifat mendidik sebagai novel remaja distopiadengan cara memberi peringatan mengenai absolutisme kelompok tertentu, bahaya dari kebijakan tertentu di masyarakat dini hari, juga pentingnya pengetahuan, individualitas, dan kebebasan untuk memilih. Kata Kunci: kontrol, pertentangan, disiplin, distopia, sastra remaja